Influence of equol and resveratrol supplementation on health-related quality of life in menopausal women: A randomized, placebo-controlled study. (February 2017) - Davinelli, Sergio; Scapagnini, Giovanni; Marzatico, Fulvio; Nobile, Vincenzo; Ferrara, Nicola; Corbi, Graziamaria
Highlights: Effects of equol and resveratrol supplementation on HRQoL were investigated in recently postmenopausal women. Postmenopausal women took equol and resveratrol or placebo daily for 12 weeks. The treatment induced an improvement in health-related quality of life, reducing some menopause-related symptoms. Abstract: Objective: This study was designed to evaluate the effects of equol and resveratrol supplementation on health-related quality of life (HRQoL) in otherwise healthy menopausal women with hot flashes, anxiety and depressive symptoms. Methods: Sixty recently menopausal women aged 50–55 years were randomized in a 12-week, placebo-controlled trial to receive 200 mg of fermented soy containing 10 mg of equol and 25 mg of resveratrol (1 tablet/day). The primary outcome was the change in score on the Menopause Rating Scale (MRS), used to evaluate the severity of age-/menopause-related complaints. Additional outcome measures included the subject-reported score on the Hamilton Rating Scale for Depression (HAM-D) and Nottingham Health Profile (NHP), which was used specifically to assess sleep quality. Results: The symptoms assessed by the MRS improved during treatment in the active group. Comparison between placebo and treatment groups revealed statistically significant improvement in particular for dryness of vagina (−85.7%) (p < 0.001), heart discomfort (−78.8%; p < 0.001) and sexual problems (−73.3%; p < 0.001). On the HAM-D significant improvements at week 12 were seen in work and activities (−94.1%) (p < 0.001). Subjects treated with equol and resveratrol also had significant differences in the sleep domain of the NHP (p < 0.001). Conclusion: These findings provide evidence that 12 weeks of dietary supplementation with equol and resveratrol may improve menopause-related quality of life in healthy women.